G3: Water governance and community based management - Mukherji, Aditi (2011)
Inundation and severe flooding in the coastal areas is a frequent occurrence in Bangladesh. This leads to loss of life and property as well as severe impacts on livelihoods. The government of Bangladesh has been investing steadily in coastal zone management through construction and rehabilitation of polders. This project is about water governance and community based management of polders in coastal zones in Bangladesh. The challenges facing the polder communities are complex and similar to those faced by many communities in which water is used for multiple purposes. But unlike other multiple use systems (such as canals, tanks), where there is rarely ever a commonality in interest, in case of polder communities, the fear that these polders may breach during a natural calamity and cause damage to life and property makes it easier to bring about a modicum of community action. However, beyond this commonality, the communities face conflicting interest. They must prioritize water use across different sectors (water for irrigation vs. water for shrimp cultivation, pond fisheries) or within the same sector (irrigation for boro crop vs. irrigation for upland crops) and also cope with prolonged periods of submergence and non-rainy days. They must also limit potential conflict between water users, as they endeavor to use water efficiently, without seriously compromising equity issues, such as those related to access to water by marginalized members of the community and women. The main objective of this research project is to understand the different modes and outcomes of water governance in selected polder sites and understand the role that communities play in such governance, conflict resolution and productive use of land and water resources. Given the complexity of issues, we will adopt a three phase research approach. In Phase I, we will conduct situation analysis in six selected polders. This will enable us to understand the different uses of water in polders, the conflicting interests arising thereof and the different governance mechanisms that are in place to manage these conflicts and their comparative advantage and disadvantages. In Phase II, we will zoom into community governance issues of two polders and do a detailed study on pros and cons of community management of polders.